Eroding the asymmetry of investment arbitration: towards a model of environmental obligations for investors - Aránguez Díaz, Pedro J. (CUADERNOS DE DERECHO TRANSNACIONAL, 2025)
Investment arbitration suffers from a legitimacy crisis with criticisms regarding the inherent asymmetry of the system, mostly comprised of State obligations without investor obligations, and the apparent inability of investment arbitration to achieve a compensatory function with respect to environmental damage caused by investors. A joint solution to address both criticisms is the design and pursuit of a model for environmental investor obligations and a procedural mechanism for their adjudication in investment arbitration. The feasibility of this reform proposal requires a systematic study of the different elements needed at the substantive and procedural level within the legal framework of investment arbitration.